DNA repair in nuclear workers after occupational exposure to ionising radiation. (24th February 2004) - Georgieva, R.; Dimitrov, B.D.; Bairakova, A.K.
Recently, for purposes of radiation safety, the validation of the linear non-threshold (LNT) hypothesis at low doses of radiation was actively discussed. New knowledge, especially on subcellular level, might contribute to the clarification of this problem. The aim of our study was to describe the patterns of spontaneous (rs_sp) and induced (rs_ind) leukocyte DNA repair in workers from the Nuclear Power Plant in Kozlodui (Bulgaria). An epidemiological cross-sectional survey was carried out. Retrospective information about demographic characteristics, health status and occupational exposure (including age at initial exposure, age at sampling, duration of exposure, radiation doses, etc.) was collected. The personnel gave informed consent to participate in the study and were assured of complete anonymity. Blood samples were taken from 342 workers (286 exposed workers in the "strict regimen" area and 56 non-exposed NPP administration staff). The annual doses of irradiation in the exposed group were within the occupational safety limits. Both the basal and repair DNA syntheses (so called unscheduled DNA synthesis) were defined in short-term culture of whole blood (before and after in vitro 2 Gy γ-irradiation). The incorporation of 3H-thymidine in the leukocyte population (in the presence or absence of oxyurea, respectively) was measured radiometrically. Data was analysed by methods of descriptive statistics, percentage distribution, ANOVA, non-parametric tests, parametric and non-parametric correlation and regression analysis. The results from the initial analyses indicated that probability distribution of most variables, although similar in exposed and control groups, was asymmetrical which required a procedure of normalisation of the parameters by log-transformation. Higher levels of spontaneous and induced DNA repair were found in the exposed than in the control group. Low, but significant positive correlation (p < 0.05) was found between the cumulative dose and spontaneous DNA repair patterns. At low levels of the cumulative dose (< 20 mSv) this disappeared and only positive associations between the age (at initial exposure and at sampling) and spontaneous DNA repair were found to be significant (p < 0.05). The present study substantiated the hypothesis that low doses of occupational ionising radiation might have elevated the DNA repair capacity of human leukocytes in the view of eventual subsequent exposure to radiation at higher doses. It could be suggested, therefore, that low levels of such occupational radiation might have stimulated the adaptive mechanisms of the complex system of DNA-damage control. However, the interpretation of our results in the sense of beneficial effects of low doses of ionising radiation (radiation hormesis) should be done with caution because it is not clear whether the cumulative errors of DNA repair might lead to malignant transformation.